English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-10-28 02:01:07 · 4 answers · asked by MANDY 1 in Science & Mathematics Mathematics

4 answers

easy
you mean x^2-6x -13 (no zero at end)
= (x-3)^2-22
so lowest value is 22 as (x-3)^2 lowest is 0 asuming x real
if x is not real any value is possible

2006-10-28 02:07:50 · answer #1 · answered by Mein Hoon Na 7 · 0 0

The first derivative of the equation x^2 - 6x - 13 is 2x - 6

Solving 2x-6 for its absolute minimum, solve the equation 2x-6=0.

You get x = 3.

Plug 3 into the original equation: (3)^2 - 6(3) - 13 = 9 - 18 - 13
and 9-18-13 = -22

So the answer is -22

2006-10-28 09:22:02 · answer #2 · answered by Dan 2 · 0 0

x^2 - 6x -13 = x^2 - 6x + 9 - 22 = (x-3)^2 - 22 >= -22
the least value is -22 when x = 3

2006-10-28 09:30:45 · answer #3 · answered by James Chan 4 · 0 0

x=(-6-4i)/2
=2(-3-2i)/2

2006-10-28 09:05:57 · answer #4 · answered by Anonymous · 0 0

fedest.com, questions and answers